2002
DOI: 10.1080/073993302753428447
|View full text |Cite
|
Sign up to set email alerts
|

Problems Experienced by Pregnant Student Nurses in the Republic of South Africa

Abstract: The purpose of this quantitative exploratory descriptive survey was to determine which problems pregnant student nurses experienced in the Northern Province (NP) of the Republic of South Africa (RSA). Questionnaires were completed by 93 pregnant student nurses in this province, indicating that the majority of them became pregnant because they lacked knowledge about contraceptives, emergency contraceptives, and termination of pregnancy (TOP) services (legalized in the RSA since 1996). They delayed seeking prena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
(4 reference statements)
1
7
0
Order By: Relevance
“…Overall, they reported that ECPs were not appropriate for women younger than 18 and admitted to denying young people access to EC. The studies from the Limpopo Province corroborate this finding and add that providers often impose age restrictions that prevent young women from accessing contraception methods 13,24 . The extent of this occurrence, however, is unknown; indeed, according to McFadyen et al 7 almost two thirds of providers felt that there was no minimum age for them to prescribe EC.…”
Section: Provider Attitudes To Ecsupporting
confidence: 74%
See 2 more Smart Citations
“…Overall, they reported that ECPs were not appropriate for women younger than 18 and admitted to denying young people access to EC. The studies from the Limpopo Province corroborate this finding and add that providers often impose age restrictions that prevent young women from accessing contraception methods 13,24 . The extent of this occurrence, however, is unknown; indeed, according to McFadyen et al 7 almost two thirds of providers felt that there was no minimum age for them to prescribe EC.…”
Section: Provider Attitudes To Ecsupporting
confidence: 74%
“…This limited knowledge of EC of health professionals themselves may, in turn, prevent them from discussing it with clients. The study of pregnant student nurses found that most (73%) had no knowledge of the method, despite being well educated and involved in health care training 24 . This lack of awareness on the part of health care professionals is likely to affect the use of EC in public sector health facilities 24 .…”
Section: Provider Knowledge Of Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the few studies that asked pregnant student nurses about their knowledge of EC, many (73%) had no knowledge of the method, despite being well educated and involved in health care training. 8 As a prelude to the development and implementation of an intervention aimed at promoting EC, we undertook a multi-part baseline study to determine the existing knowledge and use of EC amongst women aged 15-49 years attending public health facilities in three provinces of South Africa. Findings on EC knowledge and practice for all respondents show that only 22.8% of respondents had ever heard of EC, with the younger more educated women and women living in urban areas more likely to have heard of it.…”
Section: Introductionmentioning
confidence: 99%
“…A younger age of menarche would seem to be an outcome of social changes in lifestyle, sexual attitudes and practices. This may result in a longer time period during which unmarried youths have the opportunities for sexual activity, often in a pattern of a series of multi-partner relationships [7,8].…”
mentioning
confidence: 99%